Decentralized Taxation and the Size of Government: Evidence from Swiss State and Local Governments - Lars P. Feld; Gebhard Kirchgässner; Christoph A. Schaltegger (Center for Economic Studies and ifo Institute (CESifo), 2003)
According to the Leviathan-Model, fiscal federalism is seen as a binding constraint on a revenue-maximizing government. The competitive pressure of fiscal federalism is supposed to reduce public sector size as compared to unitary states. However, empirical results concerning the Leviathan hypothesis are mixed. This study uses a state and local-level panel data set of Swiss cantons from 1980 to 1998 to empirically analyze the effect of different federalist institutions on the size and structure of government revenue. Because of the considerable tax autonomy of sub-national Swiss governments, it is possible to investigate different mechanisms by which fiscal federalism may influence government size. The results indicate that tax exporting has a revenue expanding effect whereas tax competition favors a smaller size of government. Fragmentation has essentially no effect on the size of government revenue for Swiss cantons. The overall effect of revenue decentralization leads to fewer tax revenue but higher user charges. Thus, revenue decentralization favors a smaller size of government revenue and shifts government revenue from taxes to user charges.
Keywords: D70; D72; H71; 330; federalism; government revenue; tax competition; tax exporting